2022
DOI: 10.3389/fneur.2022.865970
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Chemical Exchange Saturation Transfer (GluCEST) Magnetic Resonance Imaging of Rat Brain With Acute Carbon Monoxide Poisoning

Abstract: ObjectivesTo evaluate the diagnostic and prognostic values of glutamate chemical exchange saturation transfer (GluCEST) magnetic resonance imaging as a quantitative method for pathogenetic research and clinical application of carbon monoxide (CO) poisoning-induced encephalopathy combined with the proton magnetic resonance spectroscopy (1H-MRS) and the related histopathological and behavioral changes.MethodsA total of 63 Sprague–Dawley rats were randomly divided into four groups. Group A (n = 12) was used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Xu et al demonstrated that the glutamate chemical exchange saturation transfer MRI non-invasively reflected the changes in glutamate content in the rat brain with higher sensitivity and spatial resolution and provided a pathogenetic and prognostic assessment of CO-associated encephalopathy. [ 27 ] Future studies would benefit from the use of latest technological developments to identify individuals at risk of dementia and new intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al demonstrated that the glutamate chemical exchange saturation transfer MRI non-invasively reflected the changes in glutamate content in the rat brain with higher sensitivity and spatial resolution and provided a pathogenetic and prognostic assessment of CO-associated encephalopathy. [ 27 ] Future studies would benefit from the use of latest technological developments to identify individuals at risk of dementia and new intervention strategies.…”
Section: Discussionmentioning
confidence: 99%